A Wild Roguery: Bruce Chatwin’s The Songlines Reconsidered - Nicholls, Christine (Text Matters: A Journal of Literature, Theory and Culture, 2019)
This article revisits, analyzes and critiques Bruce Chatwin’s 1987 bestseller, The Songlines, more than three decades after its publication. In Songlines, the book primarily responsible for his posthumous celebrity, Chatwin set out to explore the essence of Central and Western Desert Aboriginal Australians’ philosophical beliefs. For many readers globally, Songlines is regarded as a—if not the—definitive entry into the epistemological basis, religion, cosmology and lifeways of classical Western and Central Desert Aboriginal people. It is argued that Chatwin’s fuzzy, ill-defined use of the word-concept “songlines” has had the effect of generating more heat than light. Chatwin’s failure to recognize the economic imperative underpinning Australian desert people’s walking praxis is problematic: his own treks through foreign lands were underpropped by socioeconomic privilege. Chatwin’s ethnocentric idée fixe regarding the primacy of “walking” and “nomadism,” central to his Songlines thématique, well and truly preceded his visits to Central Australia. Walking, proclaimed Chatwin, is an elemental part of “Man’s” innate nature. It is argued that this unwavering, preconceived, essentialist belief was a self-serving construal justifying Chatwin’s own “nomadic” adventures of identity. Is it thus reasonable to regard Chatwin as a “rogue author,” an unreliable narrator? And if so, does this matter? Of greatest concern is the book’s continuing majority acceptance as a measured, accurate account of Aboriginal belief systems. With respect to Aboriginal desert people and the barely disguised individuals depicted in Songlines, is Chatwin’s book a “rogue text,” constituting an act of epistemic violence, consistent with Spivak’s usage of that term?